Long-term effect of composted tannery sludge on soil chemical and biological parameters - Araujo, Ademir Sergio Ferreira; de Melo, Wanderley José [UNESP]; Araujo, Fabio Fernando; Van den Brink, Paul J. (Springer Nature, 2020)
Composting has been recommended as a suitable alternative for recycling wastes and could improve tannery sludge (TS) before its use. However, the long-term application of composted tannery sludge (CTS) may bring concerns about its effects on soil properties and, consequently, on plants and environment, mainly when considering Cr contamination. In this study, we summarize the responses of soil chemical and biological parameters in a 10-year study with yearly applications of CTS. Chemical and biological parameters were assessed in soil samples, and the multivariate analysis method principal response curve (PRC) was used to show the temporal changes in all the biological and chemical properties caused by CTS. The PRC analysis showed different long-term response patterns of chemical and biological parameters according to the rates of CTS. Interestingly, Cr content increased strongly in the first 5 years and only increased slightly in the following 5 years. The yearly applications of CTS changed the biological and chemical parameters of the soil, negatively and positively, respectively. Organic matter, K and P, increased during the 10 years of application, while soil pH and Cr concentration increased, and soil microbial biomass and enzymes activity decreased.
Keywords: Environmental contamination; Industrial waste; Metals; Soil quality